Coastal Evolution, Geomorphic Processes and Sedimentary Records in the Anthropocene - Christopher Gomez; Deirdre E. Hart; Patrick Wassmer; Imai Kenta; Hiroki Matsui; Mariko Shimizu (Forum Geografi, 2019)
The question of whether or not we agree with the term Anthropocene becomes inconsequential when examining coastal environments. With few exceptions, anthropogenic encroachment on, and reshaping of, the global coastal zone is evident from space via multiple spectral views. Humans have become one of the dominant agents of coastal system change during the latest part of their relatively short existence, and nowhere is the humanization of coastal landscapes more evident than on islands. Using three island nations characterized by different stages and styles of coastal development – New Zealand, Japan, and Indonesia - we investigate the role of anthropogenic activity in coastal evolution, geomorphology and sediment records. Using field investigations, Geographical Information System (GIS) analyses, and mathematical and conceptual models, we reveals how anthropogenic activity influences processes at multiple time and space scales, with enduring effects. Our first anthropogenic impact investigation focusses on the potential effects of sea level rise (SLR) due to anthropogenic climate change. Using the earthquake-induced land-subsidence experienced in Christchurch, New Zealand, as a relative SLR example (‘Laboratory Christchurch’), evidence shows that coastal settlements are likely to be impacted not only at the shore but further inland via coast- connected waterways, where drainage is impeded due to an increase in the base level of that is the sea. Relative SLR makes it more difficult to evacuate water from subaerial and subsurface hydrosystems, and simulations show that future SLR is also likely to temporarily reduce some rivermouth sediment discharges, creating the potential for accelerated erosion in river-coast interface environments. In addition to flow-on effects from waterways, coastlines themselves have been highly affected by human activity over recent decades to centuries. In Tokyo, the shoreline has undergone artificial progradation, in places by more than 2 km, where concrete has supplanted mudflats, often at elevations above the hinterland of reclaimed areas. In addition to changes in Tokyo’s unconsolidated shores, consolidated coastal cliffs have been modified with the removal of natural talus buffers, again increasing the potential for erosion acceleration. Finally, in our third example, studies of the 2004 Indian Ocean tsunami and the 2011 Tohoku tsunami show that anthropogenic activities and structures play an important role in controlling the erosion and depostion of sediments during extreme events. A chronology of tsunami deposits from the Tohoku coast shows that sedimentary records from tsunami events have become thinner in recent centuries, independent of the incident tsunami wave hydrodynamics, and in relation to increasing levels of coastal plain, shoreline and nearshore development. In light of these multi-scale and multi-process effects, we argue that the Anthropocene is clearly distinguishable from the Holocene in coastal environments due to the significantly stronger signatures of human influence that characterise the former time period.